Illustrated SNA. - Pataky, Mark, 1957- (New York, United States of America : John Wiley & Sons, Inc., 1998)
"This book focuses on two items: First, it provides an introduction of SNA technology, and second, it describes the various technologies available to integrate SNA into an organization's network-centric computing environment. The brief tutorial on SNA discusses some of the historical developments of SNA. This is followed by a discussion on legacy SNA technology, including SNA addressing schemes and a description of Token Ring networks. The section on Token Ring technology was added because it has traditionally been the primary protocol of SNA LAN devices and the foundation of many of the early integration technologies. Note that while Token Ring networks are important to understand, in no way is this book focused on Token Ring, nor is this the only LAN technology available for SNA devices." (Copied from the preface).
Preface. How to use this book. Part one. The SNA network overview. Part two. NSA terms and devices. Part three. Network addressable units (NAUs): the SNA address and frame formats. Part four. SNA sessions. Part five. SNA links. Parte six. SNA LAN technology. Part seven. SNA integration technologies. Part eight. NSA summary and conclusions. Appendix. DLSw configuration notes. Index.
Consult CD (140)
Keywords: LANS -- NETWORKS; LOCAL AREA NETWORKS -- COMPUTER NETWORKS; LOCAL NETWORKS -- COMPUTER SCIENCE; SNA -- COMPUTER NETWORK ARCHITECTURE